MEDIATING ROLE OF EMPOWERMENT BETWEEN TOTAL QUALITY MANAGEMENT (TQM) AND SERVICE RECOVERY PERFORMANCE IN THE HOTEL INDUSTRY - M. Al-Ababneh, Mukhles; M. Al-Sabi, Samer; J. Al-Shakhsheer, Firas; A. Habiballah, Ma’moun (Journal of Tourism, Sustainability and Well-being, 2018)
The purpose of this research was to examine the mediating effect of empowerment on the linkage between Total Quality Management (TQM) and service recovery performance in the hotel industry. Although much has been written about TQM, empowerment and service recovery performance, but the role of empowerment as a mediator in the relationship between TQM and service recovery performance has remained a relatively unexplored research area. A 93-item questionnaire is designed to measure TQM, empowerment and service recovery amongst employees in five-star hotels in Jordan, and 254 usable questionnaires were used in this study. Principal components analysis determined the factor structure and regression analysis determined the relationships between the study’s variables. The results revealed that the TQM implementations have positive effects on empowerment and service recovery performance. Moreover, the study found the full mediating effect of empowerment in the relationship between TQM and service recovery performance. Implications, limitations and future research are discussed at the end. This study proposes model of influence of TQM in service recovery performance, whereby empowerment fully mediates this relationship.